Usability Testing Menggunakan Metode Heuristik dan End User Computing Satisfaction Pada Website Ikan Hias Menteng - Mauludani Muhammad; Agung Triayudi; Agus Iskandar (STMIK Budi Darma, 2023)
Ornamental Fish Menteng is a website that provides information services located in Sumenep Menteng. With the Menteng Ornamental Fish website, website visitors can get information on the ornamental fish they are looking for to visit, with information and recommendations and prices for ornamental fish. In this review, the authors dissect the satisfaction level of using the ornamental fish menteng website with a comparison of the Heuristic Evaluation method and the End User Computing Satisfaction (EUCS) method to find the usability level of the ornamental fish menteng website. Where in the Heuristic Evaluation method a score of 9.118 is obtained while the End User Computing Satisfaction method obtains a score of 9.292. From a comparative analysis of usability levels, the authors get recommendations in an effort to improve websites. What needs to be considered, among others, are the Aesthetic and Minimalist Design variables, the Helping users variable and the Timeliness variable.